Pengaruh Efikasi Diri terhadap Kematangan Karir Siswa SMAN 1 Rujukan Lubuklinggau - Dinda Anggraini; Endang Supraptiningsih (Bandung Conference Series: Psychology Science, 2022)
Abstract. At the time of high school, students are at a time when they are looking for information about themselves and their talents or abilities that must be collected so that efforts can help high school students in preparing their dreams for the future. Students who are in this high school level have an average age of 15 to 18 years, which is the age of adolescence which has entered the stage of transitional development from childhood to adulthood. Being a high school teenager is expected to have understood his career potential and chose the right career goal. However, this can be difficult for high school students because at this time there are problems that require students to start making decisions to continue their studies. The researcher found a phenomenon where class XI students at SMAN 1 Lubuklinggau showed behavior where there was no willingness to seek information that could be used to determine decisions in choosing further studies and career choices. This is because these students do not yet have one of the factors that support high Career Maturity, namely Self-Efficacy. So the purpose of this study is to find out how much influence Self-Efficacy has on Career Maturity in class XI students at SMAN 1 Lubuklinggau Reference. The research method used is quantitative method with simple regression analysis technique with a sample of 130 students using simple random sampling technique. The measuring instrument used was compiled by the researcher by deriving the theory of Self-Efficacy from Bandura (3) and Career Maturity from Super (24). The results showed that there was an effect of Self-Efficacy on Career Maturity, which was 0.446 or 44.6% and the rest was the influence of variables not examined. Abstrak. At the time of high school, students are at a time when they are looking for information about themselves and their talents or abilities that must be collected so that efforts can help high school students in preparing their dreams for the future. Students who are in this high school level have an average age of 15 to 18 years, which is the age of adolescence which has entered the stage of transitional development from childhood to adulthood. Being a high school teenager is expected to have understood his career potential and chose the right career goal. However, this can be difficult for high school students because at this time there are problems that require students to start making decisions to continue their studies. The researcher found a phenomenon where class XI students at SMAN 1 Lubuklinggau showed behavior where there was no willingness to seek information that could be used to determine decisions in choosing further studies and career choices. This is because these students do not yet have one of the factors that support high Career Maturity, namely Self-Efficacy. So the purpose of this study is to find out how much influence Self-Efficacy has on Career Maturity in class XI students at SMAN 1 Lubuklinggau Reference. The research method used is quantitative method with simple regression analysis technique with a sample of 130 students using simple random sampling technique. The measuring instrument used was compiled by the researcher by deriving the theory of Self-Efficacy from Bandura (3) and Career Maturity from Super (24). The results showed that there was an effect of Self-Efficacy on Career Maturity, which was 0.446 or 44.6% and the rest was the influence of variables not examined.